2013
DOI: 10.1055/s-0033-1341960
|View full text |Cite
|
Sign up to set email alerts
|

Scapholunate Instability: Proprioception and Neuromuscular Control

Abstract: From a kinetic point of view, the wrist is considered stable when it is capable of resisting load without suffering injury. Several prerequisites are necessary for the wrist to be kinetically stable: bone morphology, normal articulating surfaces, ligaments, the sensorimotor system, the muscles crossing the wrist, and all nerves connecting to ligaments and muscles. Failure of any one of these factors may result in carpal instability. The terms ?scapholunate (SL) dissociation? and ?SL instability? refer to one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 26 publications
0
16
0
3
Order By: Relevance
“…16 The terminal PIN sends proprioceptive and nociceptive branches to the distal radioulnar joint and scapholunate ligament. [17][18][19] The significance of this sensory input on wrist stability has been disputed by some study groups. [17][18][19] Nonetheless, efforts should be taken to extensor tendon injuries, which has the potential to allow early rehabilitation and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…16 The terminal PIN sends proprioceptive and nociceptive branches to the distal radioulnar joint and scapholunate ligament. [17][18][19] The significance of this sensory input on wrist stability has been disputed by some study groups. [17][18][19] Nonetheless, efforts should be taken to extensor tendon injuries, which has the potential to allow early rehabilitation and recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Afferent information is collected at the ligaments of the wrist when stretched, and results in reflex motor control stabilizing the wrist joint via the secondary muscular stabilizers 19,20. In-vivo studies using electromyography have shown that denervation of the anterior or posterior interosseous nerves can lead to dysfunction of the stabilizing reflex pathways of the wrist joint 21,22…”
Section: Anatomy and Biomechanicsmentioning
confidence: 99%
“…Maintaining intracarpal supination maintains the reduction of the scaphoid to the lunate and prevents widening of the SL gap and SL malalignment. 34 Elbow flexion and extension are permitted, but forearm rotation is blocked for a total of 8 weeks. After 8 weeks, patients are transitioned into a volar wrist splint and supination and pronation exercises begin.…”
Section: Treatmentmentioning
confidence: 99%